World economic survey 1991- 92 - United Nations (New York, 1991)
Since 1947, the World Economic Survey has provided reliable description, synthesis and interpretation of trends, emerging issues and policies in the world economy. This year, for the first time, the United Nations publishes this briefer volume, the World Economic Sur vey Reader, edited with you-the general read er in mind, allowing you quick access to the essential facts contained in the more extensive (and expensive) annual Reference Edition of the Survey. This easier-to-digest edition of the Survey reviews-as the Survey does every year-major differences in economic circum stances among countries and regions, and fore casts short-term global and regional trends. In addition to annual data, this year's special fo cus analyzes: the impact of changes in East West relations on the world economy; econo mies of post-Cold War military spending; dy namics of recent changes in the international oil market. This book has been edited to minimize reliance on statistical detail and tables, but does contain all the facts you need to understand to day's economic issues.
Keywords: Economic survey 1991- 92